Kajian Perbandingan Hukum Terhadap Larangan Perkawinan Hukum Adat Ana Wale Dan Undang-Undang No. 1 Tahun 1974 Tentang Perkawinan (Studi Kasus Di Kecamatan So’a Kabupaten Ngada) - Faustin Ye Wale; Darius Mauritsius; Chatryen M. Dju Bire (Artemis Law Journal, 2026)
A comparison of the prohibition of marriage found in the Ana Wale Customary Law with the provisions of Law No. 1/1974 on Marriage, especially in the context of the community in So'a Subdistrict, Ngada Regency. Ana Wale customary law recognizes the prohibition of marriage with the Sengi tribe based on a hereditary customary agreement known as Tura Zazi or bloody oath, which arose from historical conflicts and aims to maintain social harmony. Meanwhile, the Marriage Law stipulates prohibitions based on blood relations, consanguinity, consanguinity, and religious rules. This research uses an empirical legal method with a qualitative approach through interviews and document studies. The results show that although there are similarities in the purpose of the prohibition, namely maintaining social and moral order, there are fundamental differences in the legal basis, the form of sanctions, and in the prohibition in the Ana Wale Customary Law there is an agreement stating that the two prohibited tribes are blood relatives not based on lineage but based on a customary agreement or oath. This research contributes to the understanding of harmonization between national law and customary law and becomes a reference in the preparation of policies that are culturally just.